2012
DOI: 10.1074/jbc.m112.381301
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Expression, and Characterization of a Novel Molecular Motor, Leishmania Myosin-XXI

Abstract: Background:The chemomechanical properties of myosin-XXI, seemingly the only myosin expressed in Leishmania parasites, are unknown. Results: Recombinantly expressed full-length myosin-XXI is an active ATPase and, in the presence of calmodulin, moves actin filaments. Conclusion: Myosin-XXI is a mechanically functional molecular motor. Significance: Calmodulin-dependent regulation of myosin-XXI might be involved in the various functions of the motor in the parasite lifecycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…An unexpected finding was revealed by sequence analysis. The motor has eight potential calmodulinbinding sites, only one of which bound human calmodulin in our previous study (10). We have now identified a binding site close to the converter domain that is located within an extended dimerization site covering the entire C terminus of the molecule from the converter region to the C-terminal end.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…An unexpected finding was revealed by sequence analysis. The motor has eight potential calmodulinbinding sites, only one of which bound human calmodulin in our previous study (10). We have now identified a binding site close to the converter domain that is located within an extended dimerization site covering the entire C terminus of the molecule from the converter region to the C-terminal end.…”
Section: Discussionmentioning
confidence: 80%
“…The SEC study showed that FL-XXI heavy chain, coexpressed with high levels of calmodulin virus, was monomeric. Using the approach of Coluccio (16), we had found in a previous study that the stoichiometry between myosin-XXI heavy chain and human calmodulin was 1:1 for these conditions of expression (10). In contrast, in the absence of added calmodulin virus, most of the purified myosin-XXI sample eluted earlier, indicating the formation of dimers or higher oligomers (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations